The Level of Community Compliance Towards Prevention Efforts of COVID-19 in West Tanjung Jabung Regency, Jambi - Zulfitri Zulfitri; Misbahul Badri; Safrizal Rahman; Baidillah Zulkifli (The International Journal of Tropical Veterinary and Biomedical Research, 2021)
The COVID-19 cases in Tanjung Jabung Barat Regency, Jambi, have has risen significantly daily. This significant increase in cases illustrates that the people are less than optimal in complying with the health protocols established by the government. This phenomenon concluded that public compliance in efforts to prevent COVID-19 has a vital role in preventing the spread. This study aims to describe the level of compliance towards prevention efforts of COVID-19 in the community. We use a descriptive survey method with probability sampling techniques to obtain the data. The subjects in this study were the community of Tanjung Jabung Barat, Jambi Regency, who were17 years old with a sample size of 400 samples. Collecting data using a questionnaire in a validated form and distributed to the public via social media. The data analysis in this study is the frequency distribution analysis (univariate analysis). The results of this study shown were that 172 respondents (43.0%) had a good level of compliance, 146 respondents (36.5%) had a sufficient level of adherence, and as many as 82 respondents (20.5%) had a good level of compliance to prevent COVID-19 spreads.